The story of Karaz: A brief history of the research, and an understanding of the process of the Kura-Araxes culture in the Erzurum Highlands - Işıklı, Mehmet (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
The Kura-Araxean culture, which roughly characterizes the EBA period of the mountainous belt between the Taurus Mountains and the Caucasus, draws attention primarily with its geographical and chronological size. This cultural phenomenon, which has been influential in most of the Near Eastern geography for a long time, has been a subject that has been studied extensively by archaeologists and historians. Archaeological traces of this culture, which transcends today’s political borders, have been detected in the territory of almost more than ten countries. In this respect, culture has an important place in the cultural inventory and heritage of the Caucasus and related countries. Its geographical and chronological size is the source of both the richness and problems of this cultural phenomenon. These problems range from terminology to chronology. For example, in terms of terminology, culture has been called by different names in each region, depending on the regional dynamics throughout the research history of that region. A remarkable example in this regard is the name ‘Karaz’, which was given to the culture with the early researches in the Eastern Anatolian plateau, which is also the subject of this article. This article aims to tell a story of the ‘Karaz Culture’, from its emergence to its intelligibility, that is, its long journey.